Stability of Polymer:PCBM Thin Films under Competitive Illumination and Thermal Stress. (13th August 2018) - Pont, Sebastian; Foglia, Fabrizia; Higgins, Anthony M.; Durrant, James R.; Cabral, João T.
Abstract: The combined effects of illumination and thermal annealing on the morphological stability and photodimerization in polymer/fullerene thin films are examined. While illumination is known to cause fullerene dimerization and thermal stress their dedimerization, the operation of solar cells involves exposure to both. The competitive outcome of these factors with blends of phenyl‐C61‐butyric acid methyl ester (PCBM) and polystyrene (PS), supported on PEDOT:PSS is quantified. UV–vis spectroscopy is employed to quantify dimerization, time‐resolved neutron reflectivity to resolve the vertical composition stratification, and atomic force microscopy for demixing and coarsening in thin films. At the conventional thermal stress test temperature of 85 °C (and even up to the PS glass transition), photodimerization dominates, resulting in relative morphological stability. Prior illumination is found to result in improved stability upon high temperature annealing, compatible with the need for dedimerization to occur prior to structural relaxation. Modeling of the PCBM surface segregation data suggests that only PCBM monomers are able to diffuse and that illumination provides an effective means to control dimer population, and thus immobile fullerene fraction, in the timescales probed. The results provide a framework for understanding of the stability of organic solar cells under operating conditions. Abstract : The competitive effects of light and thermal stress on polymer:fullerene blend morphology are investigated. While light promotes fullerene dimerization, elevated temperatures cause dimer decomposition; evidently solar cells experience both. Time‐resolved neutron reflectivity and atomic force microscopy are employed to examine demixing and stratification in thin films and provide a framework for rationalizing stability under these innate environmental conditions.